2011
DOI: 10.1016/j.hrthm.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular heterogeneity of sodium current properties in adult cardiac ventricular myocytes

Abstract: BACKGROUND Sodium channel α-subunits in ventricular myocytes (VMs) segregate either to the intercalated disc, or to lateral membranes, where they associate with region-specific molecules. OBJECTIVE To determine the functional properties of sodium channels as a function of their location in the cell. METHODS Local sodium currents were recorded from adult rodent VMs and Purkinje cells using the cell-attached macropatch configuration. Electrodes were placed either in the cell midsection (M), or cell end (area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
141
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 27 publications
11
141
0
Order By: Relevance
“…We next investigated whether the reduced whole‐cell I Na originated from the midsection (LM region) and/or the end of the cell (ID region). Consistent with previous findings,9 cell‐attached measurements in Sham cardiomyocytes revealed a lower I Na amplitude and a negative shift in steady‐state inactivation in the LM compared with the ID region (Figure 3A and 3B, Figure S1, and Table 2). In TAC cardiomyocytes, I Na amplitude was reduced in LM and ID by 50% and 40%, respectively (Figure 3A and 3B, Table 2), without any changes in gating parameters between Sham and TAC (Figure 3C through 3F, Table 2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We next investigated whether the reduced whole‐cell I Na originated from the midsection (LM region) and/or the end of the cell (ID region). Consistent with previous findings,9 cell‐attached measurements in Sham cardiomyocytes revealed a lower I Na amplitude and a negative shift in steady‐state inactivation in the LM compared with the ID region (Figure 3A and 3B, Figure S1, and Table 2). In TAC cardiomyocytes, I Na amplitude was reduced in LM and ID by 50% and 40%, respectively (Figure 3A and 3B, Table 2), without any changes in gating parameters between Sham and TAC (Figure 3C through 3F, Table 2).…”
Section: Resultssupporting
confidence: 91%
“…Sodium channel clusters in various cardiomyocyte microdomains exhibit distinct current amplitudes and gating properties 9. Studies in animal models have shown differential contribution of distinct subcellular sodium channel pools to global conduction in the heart 10, 11, 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was proposed that Na + channels in the midsection (ie, at the lateral membrane) of the rodent cardiomyocyte do not contribute significantly to AP propagation under physiological conditions. 22 In ΔSIV hearts, however, significant defects in impulse propagation were detected despite retention of Na V 1.5 expression at the intercalated disks, thus confirming a functional role for the Na V 1.5 lateral membrane pool and decreasing the sole contribution of Na V 1.5 intercalated disk channels to cardiac conduction. Moreover, the increase in anisotropy in ΔSIV mouse hearts indicates that the lateral membrane Na V 1.5 pool may play a role in longitudinal conduction, but that it has a more pronounced influence on transversal propagation.…”
Section: Shy Et Al Na V 15 Regulation Via the Siv Motif In Vivo 159mentioning
confidence: 77%
“…At first sight, it is difficult to visualize the functional relationship between a structural element (the desmosome) and electrical events (arrhythmias). Recent data have helped to clarify the picture with the demonstration that some ion channels, such as the Na ϩ channel and some K ϩ channels (including Kv1.5 and Kir2.1), are enriched at the ICD (3)(4)(5). Moreover, there is growing evidence for interaction between desmosomal proteins and certain ion channels and that disruption of the desmosomal complex affects the function of these channels (4,6,7).…”
mentioning
confidence: 99%